PENGEMBANGAN SISTEM PENGENALAN EKSPRESI WAJAH MENGGUNAKAN JARINGAN SYARAF TIRUAN BACKPROPAGATION (STUDI KASUS PADA DATABASE MUG) - Zaenal Abidin (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
Expression or expression is one form of nonverbal communication that is the result of one or more movements or position of the muscles on the face and can convey the state emotion from someone to the person who observes it. Through facial expressions, then it can understand the emotions that are churning on the individual self. Facial expression is one behavioral characteristics. Use of biometrics technology system with expression characteristics face allows to recognize a person's mood or emotion. The basic components of the system facial expression analysis is face detection, facial data extraction, and facial expressions recognition. Integral projection method is used for face detection system. The fisherface method with artificial neural network approach backpropagation can be used for recognition of expression face. This method is done by two-stage process ie PCA and LDA. Where is the calculation PCA is used to reduce dimensions, whereas LDA is used to extract traits facial expression of each image. The study was conducted on the MUG that obtained the results recognition rate of 98.09%, and false positive 5.